Evolution of Guanylate Binding Protein (GBP) Genes in Muroid Rodents (Muridae and Cricetidae) Reveals an Outstanding Pattern of Gain and Loss - Côrte-Real, João Vasco; Baldauf, Hanna-Mari; Melo-Ferreira, José; Abrantes, Joana; Esteves, Pedro José (Frontiers in Immunology, 2022)
Guanylate binding proteins (GBPs) are paramount in the host immunity by providing defense against invading pathogens. Multigene families related to the immune system usually show that the duplicated genes can either undergo deletion, gain new functions, or become non-functional. We show that in muroids, the Gbp genes followed an unusual pattern of gain and loss of genes. Muroids present a high diversity and plasticity regarding Gbp synteny, with most species presenting two Gbp gene clusters. The phylogenetic analyses revealed seven different Gbps groups. Three clustered with GBP2, GBP5 and GBP6 of primates. Four new Gbp genes that appear to be exclusive to muroids were identified as Gbpa, b, c and d. A duplication event occurred in the Gbpa group in the common ancestor of Muridae and Cricetidae (~20 Mya), but both copies were deleted from the genome of Mus musculus, M. caroli and Cricetulus. Gbpb gene emerged in the ancestor of Muridae and Cricetidae and evolved independently originating Gbpb1 in Muridae, Gbpb2 and Gbpb3 in Cricetidae. Since Gbpc appears only in three species, we hypothesize that it was present in the common ancestor and deleted from most muroid genomes. The second Gbp gene cluster, Gbp6, is widespread across all muroids, indicating that this cluster emerged before the Muridae and Cricetidae radiation. An expansion of Gbp6 occurred in M. musculus and M. caroli probably to compensate the loss of Gbpa and b. Gbpd is divided in three groups and is present in most muroids suggesting that a duplication event occurred in the common ancestor of Muridae and Cricetidae. However, in Grammomys and Mus caroli, Gbpd2 is absent, and in Arvicanthis, Gbpd1 appears to have been deleted. Our results further demonstrated that primate GBP1, GBP3 and GBP7 are absent from the genome of muroids and showed that the Gbp gene annotations in muroids were incorrect. We propose a new classification based on the phylogenetic analyses and the divergence between the groups. Extrapolations to humans based on functional studies of muroid Gbps should be re-evaluated. The evolutionary analyses of muroid Gbp genes provided new insights about the evolution and function of these genes.